Implementation of Halal quality management system in small and medium scale enterprise- impact of mentoring and coaching - Wahid, Zaharah; Shohaimi, Anis Syuhaiz; Che Man, Muhammad Shaharul (Knowledge Transfer Programme, Ministry of Higher Education, Malaysia, 2016)
Globally, the market for certified Halal food and products is rising strongly. In Malaysia alone, there is US$500 billion worth of Halal business opportunities waiting to be tapped and everyone agrees the benefit of certified halal logo. However, most small and medium scale companies do not have the tools to get the job done. This paper adopts a case study approach to study the issues related to the deployment of mentoring and coaching intervention. The tools employed in this study are system gap analysis audit and simple quality control tools. The audit is deployed to garner as much information needed to make important decisions in a process of fulfilling halal requirements. While the quality control aspect is basically to create a sense of importance and satisfied in the employees. Also, to make them understand that their control function is essential to the halal product and quality of the enterprise. The human factors play an important role in making the success of this implementation. The main emphasize in this project is to transfer the knowledge effectively to the entrepreneur on the implementation of Halal requirements/standard MS1500:2009. The main hurdle encountered in this task is first the entrepreneur and his workers have an elementary level of education. Second, limited production levels due to financial constraints and marketing growth is slow. This slows down the returns which are needed for reinvestment in the project and expending the market. Third, the entrepreneur has limited knowledge on halal requirements. These have made it a tremendous challenge to mentoring and coaching the enterprise. The impact of coaching and mentoring of the company as well as graduated intern is highlighted. The use of a mentor can have a major impact on a business’s ability to grow and achieve outcomes faster than would have occurred otherwise.